Pergeseran Tadisi Sambatan ke Arah Komersialitas dan Implikasinya terhadap Pendidikan Karakter Gotong Royong di Kalurahan Giriwungu - Sumpono; Lestari, Emi Tipuk; Sukadari (Literasi: Jurnal Pendidikan Guru Indonesia, 2026)
This study aims to analyze the shift of the sambatan tradition toward commercialization in Giriwungu Village, Panggang Subdistrict, Gunungkidul Regency, to identify the factors influencing this transformation, and to analyze its implications for character education of mutual cooperation in the community, particularly among the younger generation. The sambatan tradition, as a form of mutual cooperation in Javanese society, was originally based on values of togetherness, social solidarity, and voluntary work without financial compensation. However, along with social changes and modernization, this tradition has undergone a transformation marked by the emergence of wage-based labor systems and the decline of community participation in collective activities.This research employs a qualitative approach using a case study method. Data were collected through in-depth interviews, observation, and documentation. The informants consisted of community leaders, local residents, and youth in Giriwungu Village. Data analysis was conducted through data reduction, data display, and conclusion drawing. The results of the study indicate that there has been a significant shift in the sambatan tradition from a mutual cooperation system to a more commercialized practice. Several factors contribute to this transformation, including economic pressures and increasing living demands, the influence of globalization and the rise of individualistic values, the lack of generational regeneration of traditional sambatan actors, and changes in social structure and community mobility. Furthermore, technological advancements and modern work systems have accelerated this shift. The shift of this tradition also has implications for the weakening of mutual cooperation character education, social solidarity, and locally rooted social care among community members. Nevertheless, the sambatan tradition has not completely disappeared but has instead adapted to contemporary social conditions, and still holds significant potential as a medium for character education based on local wisdom. In conclusion, the shift of the sambatan tradition toward commercialization is a complex social phenomenon influenced by multiple interrelated factors. Therefore, adaptive and collaborative preservation efforts involving the government, community, educational institutions, and the younger generation are necessary to maintain the core values of sambatan as part of local cultural identity and as a foundation of character education.